ECONOMIC EVALUATION OF INVESTMENT PROGRAMS FOR THE ENTRY OF A MANUFACTURING ENTERPRISE INTO THE LAN-CABLE MARKET IN KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The issue is considered relevant for cable production enterprises, who intend to enter new markets, engineering and design organizations, sponsors.
Keywords: economic, evaluation, investment.